Climate crisis and childhood in indigenous peoples. a critical analysis of previous studies - Sánchez , Doris (2025)
To systematize and analyze the information from the search of 80 references, and then analyze the 36 references found. To systematize and analyze information on the variables linked to the search, by economic sectors addressed by the different references, on the geographic location of the reviewed research, and on the various sectors addressed in the reviewed research. We used a methodology with a qualitative approach to data analysis and descriptive statistics. The results of the systematic review allowed us to find that only 25% of what was searched refers to Peru. We concluded that the level of education on the subject in Peru was still precarious. Therefore, it is necessary to investigate, through fieldwork, the impact of the climate crisis and its effect on the children of indigenous peoples in Peru. This will contribute to motivating research to seek solutions to its effects on the health, education, and nutrition of children in indigenous peoples.